Cognition, hallucination severity and hallucination-specific insight in neurodegenerative disorders and eye disease. Issue 2 (4th May 2022) - Montagnese, Marcella; Vignando, Miriam; Collerton, Daniel; ffytche, Dominic; Mosimann, Urs Peter; Taylor, John-Paul; daSilva Morgan, Katrina; Urwyler, Prabitha
ABSTRACT: Introduction: Hallucinations occur across neurodegenerative disorders, with increasing severity, poorer cognition and impaired hallucination-specific insight associated with worse outcomes and faster disease progression. It remains unclear how changes in cognition, temporal aspects of hallucinations, hallucination-specific insight and distress relate to each other. Methods: Extant samples of patients experiencing visual hallucinations were included in the analyses: Parkinson's Disease ( n  = 103), Parkinson's Disease Dementia ( n  = 41), Dementia with Lewy Bodies ( n  = 27) and Eye Disease ( n  = 113). We explored the relationship between factors of interest with Spearman's correlations and random-effect linear models. Results: Spearman's correlation analyses at the whole-group level showed that higher hallucination-specific insight was related to higher MMSE score ( r s  = 0.39, p  < 0.001) and less severe hallucinations ( r s  = −0.28, p  < .01). Linear mixed-models controlling for diagnostic group showed that insight was related to higher MMSE ( p  < .001), to hallucination severity ( p  = 0.003), and to VH duration ( p  = 0.04). Interestingly, insight was linked to the distress component but not the frequency component of severity. No significant relationship was found between MMSE and hallucination severity in these analyses. Conclusion: Our findings highlight the importance of hallucination-specific insight, distress and duration across groups. A better understanding of the role these factors play in VH may help with the development of future therapeutic interventions trans-diagnostically.